OPTIMALISASI PENGELOLAAN KOLEKSI PERPUSTAKAAN DI SMP NEGERI 1 BAWEN - Nur Hasni Nabila, Hanifa; Sholihah, Baqiyatush (Management of Education: Jurnal Manajemen Pendidikan Islam, 2021)
The purpose of this study was to determine the optimise of library collection management in SMP Negeri 1 Bawen. The method used in this research is descriptive qualitative. The results showed that (1) The flow of library collection management at SMP Negeri 1 Bawen was procurement, inventory, classification, cataloging, making library equipment, arranging library collections on shelves and weeding library collections. The implementation of the management of library collections is mostly carried out by the librarians of SMP Negeri 1 Bawen. (2) The implementation of library collection management at SMP Negeri 1 Bawen starting from the procurement of library collections to weeding library collections has mostly been carried out optimally and is in accordance with the provisions of library collection management standards according to laws issued by the national library, there are several processes which is still not in accordance with the standard (3) There are several obstacles in the process of managing library collections at SMP Negeri 1 Bawen, the obstacles that are often found in every management process are the lack of time and librarians in carrying out the entire process of managing library collections which causes the process of structuring collections in the library. library shelves and circulation services got a little late. (4) To remove obstacles from the process of managing library collections, the head of SMP Negeri 1 Bawen has several solutions, while the purpose of the solution of these obstacles is to optimize the management of library collections at SMP Negeri 1 Bawen.